The grifters - Frears, Stephen; Huston, Anjelica; Cusack, John, 1966-; Bening, Annette; Thompson, Jim, 1906-1977 (Santa Monica, CA : Lionsgate, 2015)
A con man, his mother, and his girlfriend all become involved in a game of deception, in which they prey on each other.
Originally released as a motion picture in 1990.
Based on the novel by Jim Thompson.
Dolby digital 5.1, wide screen 1.85:1.
Features: digital copy of the film.
Anjelica Huston, John Cusack, Annette Bening, Jan Munroe, Robert Weems.
MPAA rating: R.
Keywords: Thompson, Jim, -- 1906-1977 -- Film adaptations; Swindlers and swindling -- Drama; Triangles (Interpersonal relations) -- Drama; Crime films; Fiction films; Thriller films; Based on the book; Feature films